IDNLearn.com provides a comprehensive solution for all your question and answer needs. Discover prompt and accurate answers from our community of experienced professionals.
Sagot :
Answer:
the answer is -10
Step-by-step explanation:
-15+(-8)x(-1)+(-3)
due to order of operations,
-8x(-1)=8
-15+8+(-3)
-15+8= -7
-7+(-3)= -10
Answer:
-10
Step-by-step explanation:
-8*-1 = 8
-15+8 = -7
-7+-3 = -7-3 =-10
plz mark branliest
We appreciate your contributions to this forum. Don't forget to check back for the latest answers. Keep asking, answering, and sharing useful information. IDNLearn.com has the solutions you’re looking for. Thanks for visiting, and see you next time for more reliable information.